Specificity and sensibility of primer pair in the detection of Colletotrichum gossypii var. cephalosporioides in cotton seeds by PCR technique - Almeida, Mirella Figueiró de; Costa, Sarah da Silva; Dias, Iara Eleutéria; Siqueira, Carolina da Silva; Machado, José da Cruz (Journal of seed science, 2020)
Cotton Ramulosis (Gossypium hirsutum) is an important disease affecting cotton plantations in Brazil, and its causal agent, Colletotrichum gossypiivar.cephalosporioides(Cgc), according to the Brazilian phytosanitary authority, was considered a regulated non quarantine pest. It makes this microorganism subject to standardization in seed certification programs. The current seed health testing for detecting that pathogen in seed samples does not provide reliable results for routine analysis. On this paper, attempts were made to design specific primers for detection of Cgc associated with cotton seed. Two primer sets were selected based on the analysis of a multiple alignment of gene’s sequence encoding the glyceraldehyde 3-phosphate dehydrogenase from Cgc, C. gossypii and reference strains of the C. gloeosporioides species complex. The conserved sites unique to Cgc strains were used to design specific fragment of 140 bp. The primer specificity was confirmed by using other fungi. The primers produced a detectable band of target DNA of Cgc in all inoculum potentials of the pathogen artificially inoculated by the water restriction technique. The developed primer pair represents, therefore, a reliable and rapid mean to diagnose the Ramulosis agent in cotton seed. Resumo: A ramulose do algodão (Gossypium hirsutum), causada por Colletotrichum gossypii var. cephalosporioides (Cgc), é uma doença importante que afeta as plantações de algodão no Brasil. De acordo com as autoridades fitossanitárias brasileiras, esse organismo tem sido considerado uma praga quarentenária não regulamentada, o que faz com que ela seja objeto de padronização em programas de certificação de sementes. Neste trabalho, um par de primer foi selecionado com base na análise de um alinhamento múltiplo de sequências do gene que codifica a gliceraldeído-3-fosfato desidrogenase a partir de Cgc, C. gossypii e isolados de referência representantes de outras espécies do complexo C. gloeosporioides. Uma única região conservada de Cgc foi utilizada para desenhar um par de primer específico de 140 pb. A especificidade dos primers foi confirmada pela utilização de outros fungos isolados de semente algodão. Os primers produziram uma banda detectável de DNA de Cgc em todos os potenciais de inóculo artificialmente inoculados pela técnica de restrição hídrica. Os primers desenvolvidos representam, portanto, um meio confiável e rápido para diagnosticar Cgc em amostras de sementes de algodão.